Frozen Cartoon Film as a Learning Media to Improve the Students' Pronunciation Ability - Shilvyna Rahma; Husni Mubarok (Yayasan Karinosseff Muda Indonesia, 2021)
Pronunciation is an important factor in measuring achievement in learning speaking in English. Proof of speaking fluency by students is shown when they communicate verbally with a native speaker. This study aims to explain the use of the Frozen cartoon film as a learning medium to improve the students’ pronunciation ability. The research focuses are the Frozen 1 cartoon synopsis, the stages, and procedures for implementing the dubbing and subtitling method and screening the film using the dubbing method. This study uses a descriptive research method with a qualitative approach. Data collection was carried out by library research (library research). Sources of data in the form of written materials consist of primary data sources and secondary data sources. The validity of the data test emphasizes the validity and reliability test. The results of the study were analyzed using the content analysis method. The results showed that the cartoon